Betatrophin, elabela, asprosin, glucagon and subfatin peptides in breast tissue, blood and milk in gestational diabetes - Yavuz, Adem; Aydin, Mustafa Ata; Ugur, Kader; Aydin, Suna; Senol, Arzu; Baykus, Yakup; Aydin, Suleyman (Taylor & Francis Ltd, 2023)
We investigated the presence of asprosin (ASP), betatrophin, elabela (ELA), glucagon and subfatin (SUB) in the milk of mothers with gestational diabetes mellitus (GDM) and compared their levels with blood levels. We also investigated whether these peptides are synthesized by the breast. We investigated 12 volunteer mothers with GDM and 14 pregnant non-GDM control mothers. The peptides were measured using ELISA and their tissue localization was determined using immunohistochemistry. Breast milk contains ASP, betatrophin, ELA, glucagon and SUB. The amount of the peptides ranged from highest to the lowest in colostrum, transitional milk and mature milk. The amount of peptides in the milk was greater than for blood. The peptides, except for ELA, were increased in milk and blood by GDM. Betatrophin and ELA are synthesized in the connective tissue of the breast. ASP, glucagon and SUB are synthesized in the alveolar tissue of the breast. These peptides in breast milk may contribute to the development of the gastrointestinal tract of newborns and infants.
Keywords: Asprosin; betatrophin; breast milk; diabetes; elabela; glucagon; human; subfatin